Factors Influencing Received Social Support Among Emerging Adults With Inflammatory Bowel Disease: A Cross-Sectional Study. (November 2020) - Kamp, Kendra; Holmstrom, Amanda; Luo, Zhehui; Wyatt, Gwen; Given, Barbara
Abstract : The majority of research among individuals with inflammatory bowel disease (IBD) focuses on perceived social support. A gap exists regarding the role of received social support in self-management enhancement. The purpose of this study was to examine specific contextual factors (individual, condition-specific, and emerging adulthood factors) that influence received social support (total, informational, emotional, and tangible) among emerging adults (ages 18–29 years) with IBD. A convenience sample of 61 emerging adults with a diagnosis of IBD was obtained. An association was found between high total received social support and several individual factors such as being closer to the younger end of the age range (ages 18–29 years), married, and fully employed. When controlling for time since diagnosis and symptom interference, high tangible received social support was associated with the use of immunomodulator and biological medications. Emerging adulthood factors were not associated with total or any types of received social support. Future research could examine differences between types of social support and self-management behaviors. These findings contribute a new direction for intervention development with a focus on individual and condition-specific factors to enhance received social support and ultimately health outcomes for individuals with IBD.